The Prospect of the Readymade Garments Sector in Bangladesh: Result from Trend Analysis - Shimu, Afroza Ahammed; Islam, Md. Shahidul (American Journal of Trade and Policy, 2016)
Purpose: In Bangladesh readymade garments (RMG) sector, the backbone of the national economy is not the major sources of foreign revenue but a significant role player of the socio-economic development by creating employment opportunities, empowering women and alleviating poverty. In this regard, this paper tries to understand and analyze current situation and structure of the both knitted and woven sectors. After then, this paper predicts the future of both the export and export growth for the next five years. Methodology: In this study, data on the export and export growth had been collected from the BGMEA. Then the Least Square Method as a trend analysis had been applied to identify forecast export trend and the export growth trend of the both knitwear and woven sector separately. Microsoft excel program had been used for the estimation of the trend analysis alongside with providing predictions for the next five years. Results: The study found that the trend of both knitwear and woven export was upward. But the study also explored the downward trend of those two knitwear and woven sectors in terms of the growth rate. Moreover, the study showed that after the phasing out of MFA within 2004 and the withdrawal of quota protection, the knitwear export did not face any impediments accorded by the projection. Implication: This paper will be effective not for understanding the present structure of the RMG sector but helpful to take appropriate policies for the prosperity of the country, especially of this sector.